2018
DOI: 10.1101/500868
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assembly of functionally antagonistic visual circuits for controlling pupil dynamics

Abstract: Highlights 32 33 • Tbx20 plays a role in the development of non-image-forming pathways. 34 35 • Loss of Tbx20-expressing RGCs alters specific aspects of the pupil reflex arc. 36 37 • Previously unknown role for a specific subset of Tbx20-expressing RGCs in 38 modulating pupil size. 39 40 eTOC 41 Dhande et al. identify a novel genetic program that marks and is required for the 42 development of non-image-forming parallel visual pathways. Moreover, chemogenetic 43 activation of a specific retina-to-OPN pathway r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…We found that the OPN receives overlapping ipRGC and conventional RGC innervation, except in the contralateral shell of the OPN, which receives only ipRGC input. The function of the OPN core is not well‐understood (Dhande et al, 2018), but it is likely that ipRGCs and conventional RGCs both play a role in its visual response.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the OPN receives overlapping ipRGC and conventional RGC innervation, except in the contralateral shell of the OPN, which receives only ipRGC input. The function of the OPN core is not well‐understood (Dhande et al, 2018), but it is likely that ipRGCs and conventional RGCs both play a role in its visual response.…”
Section: Discussionmentioning
confidence: 99%